(untitled) (Innovaciones Educativas, 2020)
Customer satisfaction is a matter of great importance for any organization that wants to achieve a competitive advantage, since satisfied customers will be loyal to the company. Education institutions are no stranger to this reality. In the business context, there are different instruments to measure customer satisfaction, some of them worldwide, which have been adapted to the education context, such as the SERVQUAL and SERVPERF scales. There are instruments specifically designed to measure the satisfaction of users of education institutions focused only on public and private universities, where the interviewee is the direct user (student). The objective of the work was to develop and validate an instrument to measure satisfaction of users of education institutions in the private sector, applicable to indirect users: parents of students at basic levels, to direct users: students in high school, higher level (undergraduate and graduate) ) and to job training. The design and validation of the instrument were carried out by applying the Delphi method in two rounds, with the participation of 12 experts. The final instrument was applied to a pilot sample of 50 users. This sample was validated using Cronbach’s Alpha and a value of 0.98 was obtained. The result was an instrument with 24 items, 22 on a semantic differential scale with values from 1 to 7 and two open questions. This instrument is considered an appropriate resource that provides elements for business strategy planning to decision makers in the private education sector.